Factors Affecting Humanitarian Resilience: A Mediating Approach of Community Engagement - Nassar, Samia; Hossain, Md Billal; Tóth Naár, Zsuzsanna; Vasa, Laszlo (Decision Making: Applications in Management and Engineering, 2024)
This paper examines the factors that influence humanitarian resilience, explicitly focusing on the mediating role of community engagement. Humanitarian resilience is a critical aspect of disaster management and response, and understanding the underlying factors and the role of community engagement in enhancing resilience is paramount. This study investigates the multifaceted factors influencing humanitarian resilience among the youth population of the Gaza Strip, focusing on the variables of humanitarian aid funding, logistical support, and humanitarian personnel. Employing quantitative research methodology and Structural Equation Modelling (SEM) techniques, we explore the mediating role of community engagement in shaping the dependent variable of humanitarian resilience. In a sample of 429 youth residing in the Gaza Strip, our research assesses the direct impacts of funding humanitarian assistance, logistical support, and the presence of humanitarian personnel on the participants' resilience levels. Furthermore, we examine how community engagement mediates the relationship between these factors and the overall level of humanitarian resilience. This innovative approach aims to provide a comprehensive understanding of the intricate dynamics in the context of humanitarian assistance in the Gaza Strip. The findings of this study hold significant implications for policymakers and humanitarian organizations operating in conflict-affected regions. By elucidating the mediating influence of community engagement, we shed light on potential strategies to enhance the resilience of individuals and communities in the face of adversity, ultimately contributing to the effectiveness of humanitarian efforts in the Gaza Strip and similar contexts worldwide.